ACCOUNTING AND AUDIT ISSUES OF FINANCIAL INSTRUMENTS IN ENTERPRISES - Makhmudov Saidjamol , Kadirjanovich (THE INNOVATION ECONOMY, 2025)
The article deals with the issues of harmonization with international financial reporting standards, the solution of organizational issues of accounting for securities and the organization of audits based on international financial reporting standards.